Enabling Archaeological Hypothesis Testing in Real Time using the REVEAL Documentation and Display System - Donald H. Sanders (Virtual Archaeology Review)
This paper focuses on a system that can ensure that excavations are indeed fully documented and that the record is accurate. REVEAL is a single piece of software that coordinates all data types used at excavations with semi-automated tools that in turn can ease the process of documenting sites, trenches and objects, of recording excavation progress, of researching and analyzing the collected evidence, and even of creating 3D models and virtual worlds. Search and retrieval, and thus testing hypotheses against the excavated material happens in real time, as the excavation proceeds. That is the important advance.